Le corps des shabâb - Anna Poujeau (Ateliers d'Anthropologie)
In Syria, the category shabâb (youths), which is particularly broad and vague, designates men between the ages of around 15 and 45. If neither the calendar age (indicated by the date of birth) nor the roles assumed in the course of the individual’s existence in his kinship group (spouse, father, etc.) is enough to characterise the status or position of a shab (youth), should one wonder what this temporal social category consists of, and what place shabâb occupy in the group that otherwise broadly defines them, which in Syria is the religious group they belong to? To answer these questions, this article examines the shabâb of a community of Catholics and Greek Orthodox Christians in the Bâb Tûmâ district of Damascus and in the village of Maclûlâ, based on a comparative analysis of two major rituals that place the shabâb at the heart of the event, celebrating and emphasising two of their characteristic traits: youth and masculinity.